KRITIK BUDAYA MINANGKABAU DALAM FILM DI BAWAH LINDUNGAN KA’BAH - Diniya Khairani Aisya; Yusril Yusril; Sahrul Sahrul (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT Minangkabau culture is one of the oldest cultures in Indonesia. Minangkabau has rules that organize its people called as custom. Custom in Minangkabau is custom that philosophizes to nature because, in Minangkabau, existing customs can be altered such as nature that is always dynamic. However, there are certain parts of Minangkabau that cannot be altered. Minangkabau culture is an interesting culture to become the background of the story in the film. One of the films using Minangkabau as the background of its story is the film “Di Bawah Lindungan Ka’bah.” The film “Di Bawah Lindungan Ka’bah” is a film adapted from a novel with the same title. When watching a film, viewers will be presented pictures related to setting; acting and actors’ movement; costume and make-up, and lighting. Those four things are elements found in mise-en-scene. Mise en scene in a film determines many things such as viewers’ understanding of story delivered in the film. The mise en scene of the film “Di Bawah Lindungan Ka’bah” uses many Minangkabau elements such as rumah gadang, baju kuruang basiba (= basiba long dress), and surau. However, not all of those Minangkabau elements are accordingly suitable to describe Minangkabau culture in this film. Keywords: Minangkabau, Film, Di Bawah Lindungan Ka’bah, Mise-en-scene